Defective Bone Repair in C57Bl6 Mice With Acute Systemic Inflammation. Issue 3 (March 2017) - Behrends, D. A.; Hui, D.; Gao, C.; Awlia, A.; Al‐Saran, Y.; Li, A.; Henderson, J. E.; Martineau, P. A.
Abstract: Background: Bone repair is initiated with a local inflammatory response to injury. The presence of systemic inflammation impairs bone healing and often leads to malunion, although the underlying mechanisms remain poorly defined. Our research objective was to use a mouse model of cortical bone repair to determine the effect of systemic inflammation on cells in the bone healing microenvironment. Question/Purposes: (1) Does systemic inflammation, induced by lipopolysaccharide (LPS) administration affect the quantity and quality of regenerating bone in primary bone healing? (2) Does systemic inflammation alter vascularization and the number or activity of inflammatory cells, osteoblasts, and osteoclasts in the bone healing microenvironment? Methods: Cortical defects were drilled in the femoral diaphysis of female and male C57BL/6 mice aged 5 to 9 months that were treated with daily systemic injections of LPS or physiologic saline as control for 7 days. Mice were euthanized at 1 week (Control, n = 7; LPS, n = 8), 2 weeks (Control, n = 7; LPS, n = 8), and 6 weeks (Control, n = 9; LPS, n = 8) after surgery. The quantity (bone volume per tissue volume [BV/TV]) and microarchitecture (trabecular separation and thickness, porosity) of bone in the defect were quantified with time using microCT. The presence or activity of vascular endothelial cells (CD34), macrophages (F4/80), osteoblasts (alkaline phosphatase [ALP]), and osteoclasts (tartrate‐resistant acid phosphatase [TRAP]) were evaluated using histochemical analyses. Results: Only one of eight defects was bridged completely 6 weeks after surgery in LPS‐injected mouse bones compared with seven of nine defects in the control mouse bones (odds ratio [OR], 0.04; 95% CI, 0.003‐0.560; p = 0.007). The decrease in cortical bone in LPS‐treated mice was reflected in reduced BV/TV (21% ± 4% vs 39% ± 10%; p < 0.01), increased trabecular separation (240 ± 36 μm vs 171 ± 29 μm; p < 0.01), decreased trabecular thickness (81 ± 18 μm vs 110 ± 22 μm; p = 0.02), and porosity (79% ± 4% vs 60% ± 10%; p < 0.01) at 6 weeks postoperative. Defective healing was accompanied by decreased CD34 (1.1 ± 0.6 vs 3.4 ± 0.9; p < 0.01), ALP (1.9 ± 0.9 vs 6.1 ± 3.2; p = 0.03), and TRAP (3.3 ± 4.7 vs 7.2 ± 4.0; p = 0.01) activity, and increased F4/80 (13 ± 2.6 vs 6.8 ± 1.7; p < 0.01) activity at 2 weeks postoperative. Conclusion: The results indicate that LPS‐induced systemic inflammation reduced the amount and impaired the quality of bone regenerated in mouse femurs. The effects were associated with impaired revascularization, decreased bone turnover by osteoblasts and osteoclasts, and by increased catabolic activity by macrophages. Clinical relevance: Results from this preclinical study support clinical observations of impaired primary bone healing in patients with systemic inflammation. Based on our data, local administration of VEGF in the callus to stimulate revascularization, or transplantation of stem cells to enhance bone turnover represent potentially feasible approaches to improve outcomes in clinical practice.